Pentingnya Pembinaan Akhlak Bagi Anak Masa Pubertas - Mus Mulyadi (Institut Agama Islam Negeri Bengkulu, 2014)
This paper aims to describe how the importance of the moral development of children during puberty . It is known that ; pase puberty is an unavoidable by every child , for the normal development of children will melewat 's called puberty . Experts have been widely researched and discussed about puberty , puberty among the results is the most vulnerable period , the period of volatility in themselves anak.Oleh because it was said negative past puberty . So in this period of education into something that can not be separated , especially Islamic education . With a strong Islamic education became a bastion of the child, even the child's religious education capable menyelamat both in this world and in the hereafter .